Translanguaging by Design in EFL Classrooms. Issue 3 (2nd October 2019) - Fallas Escobar, Christian
ABSTRACT: This study presents the analysis of a translanguaging by design activity I conducted with students finishing an EFL program at a Costa Rican university, for which I showed them pictures of graffiti in Spanish and encouraged them to discuss these, using their entire linguistic repertoire. I recorded their discussions, selected instances of bilingual languaging, and analyzed their spontaneous and intuitive translanguaging. Whereas classroom interaction showed that students translanguaged for various purposes and in clearly distinctive ways, follow-up student interviews revealed some of the affordances and constraints of purposefully bringing translanguaging into programs that have for long been dominated by monolingual language ideologies. By and large, this study constitutes an attempt at transforming translanguaging from a furtive to a purposefully planned practice, which is a much-needed step forward in challenging monolingual and language separation ideologies in EFL programs and in disrupting the trend in EFL education to view students simply as learners, and not as emergent bilinguals with a complex linguistic repertoire and intricate languaging skills.